Les problèmes posés par les nématodes phytophages à l'amandier - Scotto la Massese C. (Séminaire du GREMPA sur les portes-greffes de l'amandier, 1989)
Recent research on almond genetics allows now almond growing in more varied soil types and more intensively than before. Thus, the phytopathological problems and their control are more complex. About nematodes, intensive growing increases the damage but also allows a more efficient and economical treatment. Some nematodes, as Pratylenchus, can be treated with the classical nematicides, but others, like Meloidogyne, the main pest in Mediterranean countries, can be cured by the use of resistant rootstocks, adapted to most soil types supporting almond growing. Their use requires some caution, due to the different resistance mechanism of the different species used to build up the new rootstocks. The spreading of non-endemic species by the own plants is the main origin of orchard contamination.
Séminaire du GREMPA sur les portes-greffes de l'amandier, 1988/11/29-30, Saragoza (Spain)